Rancang Bangun Alfepunic (Alat Fermentasi Pupuk Organik Cair) Terhadap Peningkatan Kualitas Hasil Pupuk Organik Cair - Ayu Hartanti, Dyah; Chusnah, Miftachul; Rosikhoh, Fahmu (AGROSAINTIFIKA, 2023)
The purpose of this study is to determine the effectiveness of the design of liquid organic fertilizer fermentation equipment (ALFEPUNIC). ALFEPUNIC is a tool specifically designed to help facilitate the anaerobic process of fermenting liquid organic fertilizer equipped with a stirrer, removable filter, faucet, hose as a drain for gas, and a sterile bottle. In this study the method used was descriptive qualitative research method with a focus on testing the fermentation tool to determine the increase in the quality of the fermented liquid organic fertilizer. The results showed that the ALFEPUNIC tool worked optimally which was marked by organoleptic from 20 respondents who gave statements, 90% said the liquid organic fertilizer did not smell strong and 75% said the color was not cloudy. The liquid organic fertilizer test from the ALFEPUNIC tool showed an increase in the growth of kale seeds which was faster than the gallon tool and those that were watered with water. Liquid organic fertilizer fermentation tool (ALFEPUNIC) can improve the quality of liquid organic fertilizer to be better than fermentation using a tool without modification (gallon).